Efficiency of Continuous Positive Airway Pressure or High-Frequency Jet Ventilation by Means a Nasooral Mask in the Treatment of Pulmonary Edema - J. Salantay; P. Torok; P. Candik; E. Drbjakova; I. Lakatos; P. Toya; P. Cicatko; J. Popadák (Общая реаниматология, 2008)
Objective: to compare the efficiency of continuous positive airway pressure (CPAP) and high-frequency jet ventilation by means of a mask (HFJV-M) in the treatment of cardiogenic edema of the lung. Design: a retrospective study. Setting: Department of Anesthesiology and Intensive Medicine, Hospital NsP, Vranov, Slovakia. Subjects and methods. A hundred and ninety-six patients with varying cardiogenic edema of the lung were divided into 3 groups according to the severity of pulmonary edema (PE). By taking into account comparable pharmacotherapy, mean airway pressure, and FiO2, the authors compared the efficiency of CPAP (n=64) and HFJV-M (n=101) from the rate of changes in respiration rate, blood oxygenation, acid-base balance, and the duration of ventilation support and the length of stay in the intensive care unit (ICU). The results were assessed by the unpaired Student’s test. The procedure of artificial ventilation via HFJV-M was approved by the Professional and Ethics Committee, Ministry of Health in the Republic of Slovakia, in 1989 for clinical application. Results. Comparison of CPAP or HFJV-M used in mild PE that was called Phase 1 of PE revealed no statistically significant differences in the parameters being assessed. In severer forms of PE characterized as Phases 2 and 3, the use of HFJV-M in the first 3 hours of ventilation maintenance caused a rapider reduction in spontaneous respiration rate from 25—33 per min to 18—22 per min (p>0.01). The application of HFJV-M also showed a statistically significant difference in the correction rate of PaO2, pH, and oxygenation index (PaO2/FIO2) (p>0.01) predominantly within the first 2 hours of therapy. Comparison of the mean duration of necessary ventilation maintenance (CPAP versus HFJV-M: 10.9 versus 6.8 hours) and the mean length of stay in the ICU (CPAP versus HFJV-N: 2.7 versus 2 days) revealed a statistically significant difference (p>0.01 and p>0.05, respectively). Only 6.6% of the HFJV-M group patients needed intubation and routine ventilation modes. Conclusion. The statistical analysis of controlled parameters (oxygenation, acid-base balance, duration of ventilation maintenance, length of hospital stay, and intubation needs) established that ventilation maintenance by HFJV-M versus CPAP was more effective just in the first 2—5 hours of therapy. When HFJV-M was used, the duration of required ventilation maintenance and the length of stay in the ICU were less since the need for intubation decreased to 6.6%.